Role of local community in tourism development: Case study village Zabrega - Belij Маrija; Veljković Јоvana; Pavlović Sanja (Glasnik Srpskog Geografskog Društva, 2014)
Studies and researches on the role of a local community in tourism development of rural areas emphasize the significance of inhabitants’ attitudes about the state and perspectives of this activity. In this context, in the professional literature, the term CBT (community-based tourism) is used, which implies the involvement of local communities and planning of tourism development. The aim of the study is to determine the local population’s influence on starting an initiative for a tourist arranging of the village Zabrega in the Municipality of Paraćin, especially the sacral objects in the Crnica River Gorge. The following methods were applied: method of direct observation, analysis, synthesis, interview and survey in which the questions were of a closed and open type. Results of the research survey were analyzed in the software package for statistical processing and analysis of the data SPSS 20.00. It has been stated that the population has a positive attitude about the Society Petrus, which is the main organizer of the activities when the prosperity of the village Zabrega is in question, and that the local community is interested in engaging in the tourist activities, as demonstrated by numerous practical examples. [Projekat Ministarstva nauke Republike Srbije, br. 176017 i br. 176008]